2016
DOI: 10.1136/heartjnl-2016-309350
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of cardiac echinococcosis

Abstract: Cardiac echinococcosis is a rare manifestation of cystic echinococcosis (CE) caused by the tapeworm Echinococcus granulosus Among all patients suffering from CE, only 0.5%-2% exhibit a cardiac involvement. In addition, during the past years the number of CE cases reported in Western Europe remained roughly unchanged. However, we postulate that cases of CE in Western Europe will increase due to a growing number of refugees coming from endemic areas such as Southern Europe, Eastern Europe and the Middle East. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
19

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 36 publications
3
70
0
19
Order By: Relevance
“…Table 1 demonstrates the differential diagnosis for intracardiac cysts. Among all cystic echinococcosis, 0.5% to 2% shows a cardiac involvement . Cardiac hydatid cysts should always be surgically removed, but there is also risk of death due to massive antigenic stimuli and pulmonary embolism after resection of the cyst, as Díaz‐Menéndez et al reported .…”
Section: Case Presentationmentioning
confidence: 96%
“…Table 1 demonstrates the differential diagnosis for intracardiac cysts. Among all cystic echinococcosis, 0.5% to 2% shows a cardiac involvement . Cardiac hydatid cysts should always be surgically removed, but there is also risk of death due to massive antigenic stimuli and pulmonary embolism after resection of the cyst, as Díaz‐Menéndez et al reported .…”
Section: Case Presentationmentioning
confidence: 96%
“…Complications are related to their size and location, mainly including haemodynamic obstruction, valve dysfunction, embolism and infective endocarditis. The cyst may rupture as it grows, especially the hydatid cyst, resulting in allergy and embolism 1. Cystic tumour of the atrioventricular node may cause heart block and sudden death 2.…”
Section: Answer: Dmentioning
confidence: 99%
“…Echinococcus de la familia Taeniidae que infecta el intestino del perro (tenia adulta), su huésped definitivo asintomático. En el hombre, su huésped intermediario incidental, un 10 % de sus huevos alcanzan la circulación, llegando a órganos específicos como los pulmones y otras ubicaciones sistémicas como el corazón, páncreas, bazo y cerebro (2,3,14,10) .…”
Section: E Granulosus Es Un Metacéstodo Ciclofilideo Del Génerounclassified
“…Una vez que el parásito alcanza al miocardio el quiste se forma entre uno a cinco años (2,5) . El ventrículo izquierdo, al recibir más flujo sanguíneo, se compromete con más frecuencia (55 % a 60 %), seguido del ventrículo derecho (15 % a 25 %), la aurícula izquierda (8 %), el pericardio (8 % a 11 %), el septum interventricular (5 % a 9 %) y arterias pulmonares (7 %) por su mayor vascularización (2)(3)(4)(5)10) . Los quistes hidatídicos del ventrículo izquierdo son usualmente localizados en el subepicardio, mientras que los del septum interventricular son intramiocárdicos (3,5,14) .…”
Section: E Granulosus Es Un Metacéstodo Ciclofilideo Del Génerounclassified